Experience on Series Production of the HL-LHC Superferric High Order Corrector Magnets - Statera, M.; Prioli, M.; Broggi, F.; De Matteis, E.; Imeri, L.; Leone, A.; Mariotto, S.; Paccalini, A.; Pasini, A.; Pedrini, D.; Rossi, L.; Sorbi, M.; et al. (IEEE transactions on applied superconductivity, 2023)
INFN has developed at the LASA lab (Milano, Italy) the High Order (HO) corrector magnets for the High Luminosity-LHC (HL-LHC) project, which will equip the new interaction regions. All the HO correctors, from skew quadrupole to dodecapole, are based on a novel superferric design, never used so far in high energy colliders, which allows a relatively simple, modular, and easy way to construct a magnet. After the completion of the production of the 54 series magnets in industry, the powering of all the produced magnets has been achieved. The delivery to CERN and the assembly of the first cold mass started. Each magnet has been powered individually and most of them have also been magnetically characterized, the aggregate results are presented and discussed. The lessons learned during the production and the testing of the magnets are reported. The quality assurance and the procedures developed in during development and production in industry proved to be key points of the successful experience of the HO correctors development, together with the solid design. We also report the lessons learned during the experience of the series production of the HO correctors.